CPEC and Marine Environmental Sustainability: Assessing the Ecological Impact of Port and Shipping Development in Gwadar (Qualitative Research Journal for Social Studies, 2025)
The China–Pakistan Economic Corridor (CPEC), a flagship project of the Belt and Road Initiative, has transformed Gwadar into a strategic maritime hub. While this development promises economic growth through trade, industrialization, and employment, it simultaneously threatens Pakistan’s fragile coastal ecosystems. This paper provides the first integrated legal-ecological assessment of Gwadar’s port expansion, critically examining the environmental consequences of dredging, shipping traffic, and industrial activity. It situates these impacts within Pakistan’s national legislation, including the Pakistan Environmental Protection Act (1997), and international obligations under UNCLOS, MARPOL, and the Convention on Biological Diversity. The analysis reveals persistent gaps in enforcement, institutional capacity, and stakeholder participation, underscoring the tension between economic ambition and ecological responsibility. The study concludes that sustainable port development under CPEC requires stronger regulatory compliance, regional cooperation, and the embedding of environmental safeguards into broader economic planning, positioning Gwadar as a test case for balancing Belt and Road growth with marine sustainability.